Induced abortion after advent of fetal sex detection technology and child sex at birth - Ruchira Tabassum Naved; Jannatul Ferdous Antu; Kausar Parvin; M. Moinuddin Haider; Syed Manzoor Ahmed Hanifi (BMC Public Health, 2024)
Abstract Background National level Sex Ratio at Birth (SRB) is normal in Bangladesh despite its patriarchal social structures, strong son preference, and low fertility level, widely recognized as preconditions for Gender-Biased Sex Selection (GBSS). To better understand this anomaly, we examine the trend in SRB in a sub-district in Bangladesh and assess the impact of the introduction of fetal sex-detection technology and the history of induced abortion on child sex using longitudinal data. Methods We have used secondary data collected routinely by icddr, b’s Matlab Health and Demographic Surveillance System (HDSS) between 1982 and 2018. All births occurring during this period (N = 206,390) were included in the analyses. We calculated the SRB and used multivariate logistic regression analyses to assess the likelihood of birth of a male child before and after the introduction of ultrasonogram in Matlab. Results Overall, SRB was within the natural limit (106) during 1982–2018 in Matlab. SRB among women with a history of induced abortion was 109.3 before the introduction of ultrasonography in 2001 and 113.5 – after 2001. Women’s history of induced abortion prior to introduction of ultrasonogram (1982–2000) increased the likelihood of birth of a male child 1.06 times (AOR 1.06; 95% CI- 1.01–1.11). In the period after, however, this likelihood was 1.08 (AOR 1.08; 95% CI- 1.02–1.15). Conclusions In a context with normal SRB, it was found to be skewed among women who had induced abortion. SRB was relatively more skewed among such women after the advent of ultrasonogram compared to a period without ultrasonogram. Moreover, induced abortion after introduction of fetal sex determination technology increased the likelihood of birth of a male child. These findings suggest the plausibility of GBSS in a sub-group. Further research is needed, particularly in regions with skewed SRB to examine whether GBSS is indeed a threat to Bangladesh.